Fiscal sustainability and the State Oil Fund in Azerbaijan - Kenan Aslanli (Journal of Eurasian Studies, 2015)
Azerbaijan, like many resource-rich countries, decided to set up a sovereign wealth fund in order to avoid income volatility, to achieve intergenerational equity and to transform resource wealth into more productive assets. Azerbaijan established the State Oil Fund of the Azerbaijan Republic (SOFAZ) in late 1999 to accumulate income from hydrocarbon exports. SOFAZ has gradually become the leading part of the country's public finance system. Azerbaijan was the first country to fulfill all requirements of the Extractive Industries Transparency Initiative (EITI), an international agreement to implement global standards of transparency in the resource extracting sectors. However, SOFAZ's contribution to an effective resource revenue management and long-run economic development is still questionable: transparency applies only to the income side of Azerbaijan's oil fund while the expenditure side remains opaque. Unlimited and unconditional transfers from SOFAZ to the state budget have threatened fiscal sustainability and the overall macroeconomic equilibrium.